Masters of disaster : the ten commandments of damage control - Lehane, Christopher; Fabiani, Mark.; Guttentag, William (New York : Palgrave Macmillan, 2012)
Whether you're a politician caught with his pants down, a publicly traded company accused of accounting improprieties, a family-owned restaurant with a lousy Yelp review or just the guy in the corner cubicle who inadvertently pushed "reply all," a crisis doesn't have to be the make-or-break moment of your career. For those of us that aren't natural spin doctors, it's hard to resist the impulse to cover your tracks, lie, or act like nothing happened. But resist you must. Full of both lively personal anecdotes and hard-knuckled straight talk, this is a must-read for anyone who wants to emerge with their reputation intact.
Crisis as a state of nature -- Stop digging -- Do no harm -- Discipline -- Credibility -- Playing to win -- Commandment I : full disclosure -- Commandment II : speak to your core audience -- Commandment III : don't feed the fire -- Commandment IV : details matter -- Commandment V : hold your head high -- Commandment VI : be straight about what you know, what you don't know, and what you are going to do to fix the problem -- Commandment VII : respond with overwhelming force -- Commandment VIII : first in, first out -- Commandment IX : no swiftboating -- Commandment X : they dissemble, you destroy -- The damage control survival kit -- The user's manual.
Includes index.
Keywords: Crisis management; Public relations; Publicity; Reputation; Marketing -- Management